Initial Assessment Learning to Identify Trauma Emergencies using Audiovisual media Effectively improves Cognitive Skills - Ani Sutriningsih; Vita Maryah Ardiyani; Wahyu Dini Metrikayanto; Remigio Halek Alves; Sri Haryuni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
As prospective professional nurses, nursing students need to take appropriate initial action (initial assessment) to avoid errors in practice. This pre-experimental study aimed to determine the effectiveness of an audio-visual initial assessment method in improving cognitive and psychomotor identification of trauma emergencies in nursing students. The research design used was pre-experimental with a pre-and post-test approach. The independent variable was the audio-visual learning method, while the dependent variables were cognitive and psychomotor initial assessment. The sample of this study comprised 6th semester students in the 2023/2024 academic year who took the Emergency Nursing course at University of Tribhuwana Tunggadewi. A total of 57 students who met the inclusion criteria were selected using simple random sampling. The instruments for measuring cognitive and psychomotor initial assessment were questionnaires and observation sheets. Interventions were implemented through learning activities utilizing the audio-visual method. Analysis was conducted using Wilcoxon test. The results showed that the average cognitive score before learning 56.49 which increased to 66.27 after learning the initial assessment of trauma emergency identification using audio-visual media. The average psychomotor score before learning was 59.64 which increased to 67.19 after the same learning intervention. These results indicated a significant increase in both cognitive and psychomotor scores (p 0.001). Learning using audiovisual media is recommended to improve initial emergency nursing skills. The greater the nurse's knowledge of initial assessment, the better the primary survey will be implemented, thereby reducing patient mortality and disability.